Quantitative Determination Of Ketorolac Tromethmine From Ophthalmic Eye Drop Formulation By Uv-Spectrophotometry - Gupta, Santosh Kumar; Arora, P.; Yadav, R. (Asian Journal of Pharmaceutical Research and Development, 2014)
A simple, accurate and economical UV-Spectrophotometric method has been developed for routine analysis of ketorolac tromethmine (KT) in ophthalmic solution. In saline phosphate buffer (PBS) pH 7.2 and simulated tear fluid (STF)/bicarbonate ringer solution pH 7.2, Ketorolac tromethmine showed maximum absorbance at 316.0 nm. In this method Ketorolac tromethmine obeyed linearity in the concentration range of 1 - 10 μg/mL (r2 > 0.99). Proposed methods were applied for ophthalmic solution and amounts of ketorolac tromethmine estimated by this method were 99.91 ± 1, 99.46 ± 1 in phosphate buffer and in simulated tear fluid respectively. Methods were validated statistically.